The challenges of designing an ESP course: Perceptions of EFL trainee teachers in the city of Buenos Aires - Falasca, Marina (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2024)
This research article presents findings from an exploratory study on the perceptions of 25 EFL trainee teachers in the city of Buenos Aires regarding the main difficulties they faced when designing their first English for Specific Purposes (ESP) course not centered around reading comprehension. Participant responses reveal several recurring challenges including the integration of ESP knowledge into general language teaching, the complexities surrounding curriculum development and needs assessment, the strategic alignment of tasks and assessments with learner objectives, considerations of diverse learning styles, and a balanced view on the role of basic language skills in ESP learning outcomes. These findings reinforce the need for ongoing professional development and institutional support to empower future ESP instructors to design effective ESP courses tailored to different professional and academic needs beyond reading comprehension.